The ETFL formulation allows multi-omics integration in thermodynamics-compliant metabolism and expression models - Pierre Salvy (Nature Portfolio, 2020)
Accounting for the effects of genetic expression in genome-scale metabolic models is challenging. Here, the authors introduce a model formulation that efficiently simulates thermodynamic-compliant fluxes, enzyme and mRNA concentration levels, allowing omics integration and broad analysis of in silico cellular physiology.